2006
DOI: 10.1002/app.23039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of support material on ultrafiltration membrane performance

Abstract: Supported ultrafiltration (UF) membranes based on polyacrylonitrile were prepared by phase inversion method using nonwoven polyester fabric as support with different origin. The membrane preparation parameters, including dope solution composition and casting conditions, were kept same while changing the support fabric. Various analyses performed, viz. water flux, protein rejection, porosity, and membrane compaction indicated that the support used for UF membrane preparation affects the membrane properties to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The compaction effect of membrane substrate was evaluated using an adapted method from references [29][30][31]. Briefly, a membrane substrate coupon with an effective area of 42 cm 2 was mounted inside a cross-flow testing cell (CF42 Membrane Cell, Sterlitech).…”
Section: Evaluation Of Compaction Effect Of Membrane Substratesmentioning
confidence: 99%
“…The compaction effect of membrane substrate was evaluated using an adapted method from references [29][30][31]. Briefly, a membrane substrate coupon with an effective area of 42 cm 2 was mounted inside a cross-flow testing cell (CF42 Membrane Cell, Sterlitech).…”
Section: Evaluation Of Compaction Effect Of Membrane Substratesmentioning
confidence: 99%
“…In case of PSF-dope solution, gelation was done at 6-8 • C in water and curing at 60 • C. The formed membranes were washed under running water for 12 h. The membranes were designated as PAN 15 , PAN 17 , PAN 20 and PSF 20 ; where the suffix denotes the concentration of polymer in the dope solution. These UF membranes were characterized for water flux, bubble point and solute rejection using proteins of different molecular weight (0.1% aqueous solution at 7.5 pH using McIlvaine buffer) as detailed earlier [19]. These UF membranes were preserved at 4 • C with 0.1% formalin until use.…”
Section: Preparation and Conditioning Of Uf Support Membranementioning
confidence: 99%
“…McCutcheon and Elimelech also studied the effect of using a fabric support during membrane fabrication and reported that membranes without the fabric had a steady flux over time compared to membranes with a fabric which showed a decline in flux that was attributed to the fabric preventing full wetting of the TFC membrane [27]. Lohokare et al monitored the change in performance of a polyacrylonitrile ultrafiltration (UF) membrane using woven and nonwoven fabrics [28]. They found that woven fabrics gave higher flux, reduced protein rejection and higher compaction resistance under hydraulic pressure.…”
Section: Introductionmentioning
confidence: 96%